2004
DOI: 10.1029/2004gl020486
|View full text |Cite
|
Sign up to set email alerts
|

Coupling effect of the equatorial F region irregularities on the low latitude E region instability processes

Abstract: Simultaneous observations of E and F region irregularities made using the Gadanki MST radar are presented. The observations show that the E region echoes weaken or disappear during the growth phase of the topside F region irregularities. Unlike Jicamarca observations, no valley region echoes are observed during this phase. It is shown that the weakening or disappearance of E region signals are not directly coupled with the F region irregularities just overhead, but linked with the instability processes over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 17 publications
4
33
0
Order By: Relevance
“…10a and b show the occurrence of E region echoes corresponding to ESF plume events and without overhead ESF, respectively, based on Gadanki radar observations. These results are quite similar to those reported by Patra et al (2004b) except the fact that the results shown in Fig. 10a are generated with clear cases of radar plumes observed in the early part of nights in the Gadanki radar observations.…”
Section: E Region Aspectssupporting
confidence: 91%
See 1 more Smart Citation
“…10a and b show the occurrence of E region echoes corresponding to ESF plume events and without overhead ESF, respectively, based on Gadanki radar observations. These results are quite similar to those reported by Patra et al (2004b) except the fact that the results shown in Fig. 10a are generated with clear cases of radar plumes observed in the early part of nights in the Gadanki radar observations.…”
Section: E Region Aspectssupporting
confidence: 91%
“…Based on Gadanki radar observations, Patra et al (2004b) evaluated the disruption of E region echoes in connection with ESF plumes reported earlier by Hysell et al (1994) and Rao et al (1997). They showed that the E region echoes are disrupted when the high altitude plumes with upward drifts are observed.…”
Section: E Region Aspectsmentioning
confidence: 99%
“…Kelley et al (2002) and Ostuka et al (2002) have detected the effects of equatorial bubble at far off-equatorial latitude stations. The low-latitude observations from Indian MST and EAR radars (Patra et al, 2004;Yokoyama et al, 2005) reveal the presence of valley region echoes and suppression of E region irregularities. These phenomena are again linked to the polarization field of equatorial bubble (Patra et al, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…In the NS plane they can point perpendicular to the magnetic field at both E-and Fregion altitudes and obtain echoes from both regions simultaneously. By doing so they find that whenever Spread F bubbles appear, the E-region echoes weaken or disappear (Patra et al, 2004), as seen in Fig. 16.…”
Section: Satellites Rockets and Other Radars And Radar Techniquesmentioning
confidence: 81%